1997
DOI: 10.1046/j.1365-2958.1997.3811764.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis DivIVA protein targets to the division septum and controls the site specificity of cell division

Abstract: SummaryThe Bacillus subtilis divIVA gene, first defined by a mutation giving rise to anucleate minicells, has been cloned and characterized. Depletion of DivIVA leads to inhibition of the initiation of cell division. The residual divisions that do occur are abnormally placed and sometimes misorientated relative to the long axis of the cell. The DivIVA phenotype can be suppressed by disruption of the MinCD division inhibitor, suggesting that DivIVA controls the topological specificity of MinCD action and thus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
311
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(324 citation statements)
references
References 26 publications
(51 reference statements)
12
311
0
1
Order By: Relevance
“…Interestingly, one of these with similar domain organisation is DivIVA, another bacterial cytoskeletal protein that is essential for polarised growth in Actinomycetes (Flardh, 2003;Letek et al, 2008) whilst it controls cell division in others, such as Bacillus subtilis (Edwards et al, 2000;Edwards and Errington, 1997). It will be of great interest to establish to what extent Scy, FilP and DivIVA might share structural characteristics with potential relevance to their biological function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of these with similar domain organisation is DivIVA, another bacterial cytoskeletal protein that is essential for polarised growth in Actinomycetes (Flardh, 2003;Letek et al, 2008) whilst it controls cell division in others, such as Bacillus subtilis (Edwards et al, 2000;Edwards and Errington, 1997). It will be of great interest to establish to what extent Scy, FilP and DivIVA might share structural characteristics with potential relevance to their biological function.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of investigation provided insight into the genetic control of axial filament formation. The first was a study of the DivIVA protein of B. subtilis, considered the functional homologue of Escherichia coli MinE in that it restricts the division-inhibition proteins MinCD to the cell poles and so ensures mid-cell division during vegetative growth (34,56). divIVA mutants have severe growth and sporulation defects, but the isolation of mutants specifically defective in sporulation suggested that DivIVA played a dedicated role in development (Fig.…”
Section: Genetic Controlmentioning
confidence: 99%
“…The result is that the mid-cell is left free for formation of the division plane. In the Gram-positive bacteria, including B. subtilis, a different topological specificity factor, DivIVA, achieves a similar result by recruiting the inhibitor to the cell poles and retaining it there (Cha & Stewart 1997;Edwards & Errington 1997;Marston et al 1998). In the presence of ATP, MinD binds to the division inhibitor MinC and goes to the membrane (Hu et al 1999Lackner et al 2003).…”
Section: A Common Mechanism Of Atp-dependent Dimerization and Atpase mentioning
confidence: 99%